Subanaesthetic ketamine and altered states of consciousness in humans - Vlisides, P.E. (Br J Anaesth, 2018)
BACKGROUND: Despite its designation as a ‘dissociative anaesthetic,’ the dissociative and psychoactive effects of ketamine remain incompletely understood. The goal of this study was to characterise the subjective experiences and accompanying EEG changes with subanaesthetic doses of ketamine. METHODS: High-density EEG was recorded in 15 human volunteers before, during, and after subanaesthetic ketamine infusion (0.5 mg kg(−1) over 40 min), with self-reported measures of altered states of consciousness obtained after ketamine exposure. Sensor- and source-level EEG changes were analysed with a focus on spectral power and regional changes. RESULTS: Ketamine-induced altered states were characterised predominantly by dissociative experiences such as disembodiment and ego transcendence; sensory disturbances were also common. Ketamine broadly decreased low-frequency power, with mean reductions largest at alpha (8–12 Hz) in parietal (−0.94 dB, P<0.001) and occipital (−1.8 dB, P<0.001) channel clusters. Significant decreases in alpha were identified in the precuneus and temporal-parietal junction. CONCLUSIONS: Ketamine induces altered states of consciousness during periods of reduced alpha power in the precuneus and temporal-parietal junction. Modulation of these temporal-parietal loci are candidate mechanisms of the psychoactive effects of ketamine, given that this region is involved in multisensory integration, body representation, and consciousness.